Genetic instability persists in non-neoplastic urothelial cells from patients with a history of urothelial cell carcinoma - Marcondes, João Paulo De Castro (2022)
301079/2009-9, to D. M. F. S.) and Coordenação de Aperfeiçoamento de Pessoal de Nível superior (CAPES, fellowship to J. P. C. M.). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.